Merging NMR Data and Computation Facilitates Data-Centered Research - Baskaran, Kumaran; Craft, D. Levi; Eghbalnia, Hamid R.; Gryk, Michael R.; Hoch, Jeffrey C.; Maciejewski, Mark W.; Schuyler, Adam D.; Wedell, Jonathan R.; Wilburn, Colin W. (Frontiers in Molecular Biosciences, 2022)
The Biological Magnetic Resonance Data Bank (BMRB) has served the NMR structural biology community for 40 years, and has been instrumental in the development of many widely-used tools. It fosters the reuse of data resources in structural biology by embodying the FAIR data principles (Findable, Accessible, Inter-operable, and Re-usable). NMRbox is less than a decade old, but complements BMRB by providing NMR software and high-performance computing resources, facilitating the reuse of software resources. BMRB and NMRbox both facilitate reproducible research. NMRbox also fosters the development and deployment of complex meta-software. Combining BMRB and NMRbox helps speed and simplify workflows that utilize BMRB, and enables facile federation of BMRB with other data repositories. Utilization of BMRB and NMRbox in tandem will enable additional advances, such as machine learning, that are poised to become increasingly powerful.